Ewing sarcoma: diagnosis, treatment, clinical challenges and future perspectives - Zöllner, Stefan K.; Amatruda, James F.; Bauer, Sebastian; Collaud, Stéphane; de Álava, Enrique; DuBois, Steven G.; Hardes, Jendrik; Hartmann, Wolfgang; Kovar, Heinrich; Metzler, Markus; Shulman, David S.; Streitbürger, Arne; et al. (Journal of Clinical Medicine, 2021)
Ewing sarcoma, a highly aggressive bone and soft-tissue cancer, is considered a prime example of the paradigms of a translocation-positive sarcoma: a genetically rather simple disease with a specific and neomorphic-potential therapeutic target, whose oncogenic role was irrefutably defined decades ago. This is a disease that by definition has micrometastatic disease at diagnosis and a dismal prognosis for patients with macrometastatic or recurrent disease. International collaborations have defined the current standard of care in prospective studies, delivering multiple cycles of systemic therapy combined with local treatment; both are associated with significant morbidity that may result in strong psychological and physical burden for survivors. Nevertheless, the combination of non-directed chemotherapeutics and ever-evolving local modalities nowadays achieve a realistic chance of cure for the majority of patients with Ewing sarcoma. In this review, we focus on the current standard of diagnosis and treatment while attempting to answer some of the most pressing questions in clinical practice. In addition, this review provides scientific answers to clinical phenomena and occasionally defines the resulting translational studies needed to overcome the hurdle of treatment-associated morbidities and, most importantly, non-survival.